Efektivitas Pelayanan Publik Pada Layanan Oke Masyarakat Keliling (Lomak) di Kecamatan Rumbai Barat Kota Pekanbaru - Yayu Ade Irma; Zulkarnaini Zulkarnaini (Jurnal Ilmiah Wahana Pendidikan, 2022)
In providing the best service to the community, the Pekanbaru City government realizes good public services with the concept of a smart city civil so that the government is required to create innovations in the field of public services in order to provide services that are transparent, accountable and accessible to the entire community. Especially at the sub-district level which is in direct contact with the community, this requires an easy transition of services in order to achieve the goals of public services. One of the public services is the Mobile Community Okay Service (LOMAK). The OK Mobile Community Service (LOMAK) is a service for managing various kinds of administration. The purpose of this study is to determine the effectiveness of public services in the District of West Rumbai, as well as the inhibiting factors in their implementation. This study uses a qualitative research method with a descriptive approach. The results in this study are the effectiveness of public services has not run optimally because the service has not worked effectively and efficiently, because it has obstacles in its implementation in the form of the Covid-19 Pandemic disaster, Lack of Awareness and Changes in Names and District Areas